A radiomics-based nomogram for the preoperative prediction of posthepatectomy liver failure in patients with hepatocellular carcinoma. (March 2019) - Cai, Wei; He, Baochun; Hu, Min; Zhang, Wenyu; Xiao, Deqiang; Yu, Hao; Song, Qi; Xiang, Nan; Yang, Jian; He, Songsheng; Huang, Yaohuan; Huang, Wenjie; et al.
Abstract: Objectives: To develop and validate a radiomics-based nomogram for the preoperative prediction of posthepatectomy liver failure (PHLF) in patients with hepatocellular carcinoma (HCC). Methods: One hundred twelve consecutive HCC patients who underwent hepatectomy were included in the study pool (training cohort: n = 80, validation cohort: n = 32), and another 13 patients were included in a pilot prospective analysis. A total of 713 radiomics features were extracted from portal-phase computed tomography (CT) images. A logistic regression was used to construct a radiomics score (Rad-score). Then a nomogram, including Rad-score and other risk factors, was built with a multivariate logistic regression model. The discrimination, calibration and clinical utility of nomogram were evaluated. Results: The Rad-score could predict PHLF with an AUC of 0.822 (95% CI, 0.726–0.917) in the training cohort and of 0.762 (95% CI, 0.576–0.948) in the validation cohort; however, the approach could not completely outmatch the existing methods (CP [Child-Pugh], MELD [Model of End Stage Liver Disease], ALBI [albumin-bilirubin]). The individual predictive nomogram that included the Rad-score, MELD and performance status (PS) showed better discrimination with an AUC of 0.864 (95% CI, 0.786–0.942), which was higher than the AUCs of the conventional methods (nomogram vs CP, MELD, and ALBI at P < 0.001, P < 0.005, and P < 0.005, respectively). In the validation cohort, the nomogram discrimination was also superior to those of the other three methods (AUC: 0.896; 95% CI, 0.774–1.000). The calibration curves showed good agreement in both cohorts, and the decision curve analysis of the entire cohort revealed that the nomogram was clinically useful. A pilot prospective analysis showed that the radiomics nomogram could predict PHLF with an AUC of 0.833 (95% CI, 0.591–1.000). Conclusions: A nomogram based on the Rad-score, MELD, and PS can predict PHLF. Highlights: Hepatectomy is a mainstay of treatment for patients with hepatocellular carcinoma (HCC). Identification of patients at risk of posthepatectomy liver failure (PHLF) before surgery is important. PHLF could be accurately predicted in a radiomics approach at low cost.